Exploring the role of reluctant altruism on charitable donations - Bradley, Alexander (2018)
Humans are remarkable for the level of altruistic and prosocial behaviour they display. This has been an enduring puzzle to social scientists who have proposed a range of theories to try to account for human’s propensity to act altruistically. This thesis adds to this tradition by exploring a new altruistic preference, known as, reluctant altruism. Reluctant altruists are those who do not trust others to help and display a positive response to high free riding contexts. Chapter one reviews the main influential theories that seek to explain altruistic behaviour and introduces the theory of reluctant altruism. Chapters two to five empirically tests core characteristics of reluctant altruism within a university population. Chapter two attempts to identify whether reluctant altruists choose to support the least supported charity and if observable contexts enhance reluctant altruist’s prosocial behaviour. Chapter two shows a clear preference for the least supported charity which is not explained by reluctant altruism or levels of observability. Chapter three tests whether reluctant altruism predicts less trusting helping behaviour in a modified trust game and identifies if reluctant altruists donate more under observable conditions with a larger sample than chapter two. The results show a clear preference for the least supported charity but find no evidence for reluctant altruists displaying less trusting helping behaviour or reluctant altruists donating more in observable contexts. Chapter four tests if reluctant altruists make charitable donations to causes suffering from varying levels of free riding. The findings again show a preference for donating to the least supported charity and displays mixed evidence for reluctant altruist’s donating under high levels of free riding. Chapter five explores reluctant altruist’s emotional responses pre and post charitable donations. The results indicate that reluctant altruists are more negative pre-donation and do not become happier post donation as might be expected by Negative State Relief theory. Chapter 6, utilises the underdog preference which is a preference to support those at a relative disadvantage to explain the consistent finding over chapters two to four that the least supported charity receives more donations. Chapter seven presents a systematic review and meta-analysis of the effect the observability has on prosocial behaviour. The main finding is the observability has a small positive effect on prosocial behaviour. Finally, in the discussion, I review the mixed findings surrounding reluctant altruism and suggest future avenues of research that might help further clarify reluctant altruism.